Optimization of Transmission Systems in Rice Threshers and Straw Choppers: Enhancing Energy Efficiency and Productivity through V-Belt and Pulley Design - Ahcmad Fauzan; Fauzi Abdillah; Abdul Muchlis (Asosiasi Dosen Muda Indonesia, 2026)
Rice threshers and straw choppers are essential to improve post-harvest efficiency, yet small-scale machines often experience capacity loss and wasted motor power due to non-optimal V-belt–pulley transmission design (e.g., incorrect pulley ratio, belt length, and speed matching), which reduces speed stability and increases mechanical losses. Objective: This study aims to analyze and optimize the V-belt–pulley transmission system of a combined rice thresher–straw chopper to improve power utilization and achieve target operating speeds for both processes. Methodology: A quantitative engineering approach was applied using analytical transmission design calculations and design verification through mechanical layout/simulation. Key parameters were derived from machine requirements and transmission relations, including processing capacity, force and torque, shaft speed, power demand, pulley diameters, transmission ratios, belt speed, belt length, center distance, and wrap angle. Findings: Using a 1 HP (750 W), 1450 rpm electric motor, the designed system achieved a calculated threshing capacity of 90 kg/h and straw chopping capacity of 84 kg/h under a 2-minute batch assumption. The required output power was 270.60 W (threshing) and 245.97 W (chopping), while the motor-side power demand was 308.27 W and 280.30 W, respectively, resulting in a total requirement of 588.57 W (≈78% motor power utilization). With an 80 mm driver pulley, the selected driven pulleys were 105.45 mm for the thresher (1100 rpm; ratio 1.32) and 116 mm for the chopper (1000 rpm; ratio 1.45). The belt speed was 6.06 m/s, with belt lengths of 2110 mm (A83) and 1480 mm (A58). Implications: The results provide practical parameter benchmarks for designing low-cost small-scale agricultural machines that better match motor power to required speeds and torque, reducing transmission mismatch. Originality: This study presents a parameter-complete V-belt–pulley design framework for a dual-function thresher–chopper, explicitly linking capacity targets to transmission sizing and motor power utilization.